THE RELATIONSHIP OF THE QUALITY OF SCHOOL LIFE WITH THE TRUTCHING BEHAVIOR OF PRIVATE HIGH SCHOOL STUDENTS IN KURANJI DISTRICT, PADANG CITY - Al Ghazali, Jihad; Aulia, Farah (In Trend : International Journal of Trends in Global Psychological Science and Education, 2023)
Truant behavior is a problem in the world of education that has a negative impact on students, such as missing lessons and being expelled from school. The aim of this research was to determine the relationship between the quality of school life and truant behavior. This research is a quantitative correlation type research. Data collection techniques in this research were a quality of school life scale and a truant behavior scale. The research subjects of this study were 62 grade 11 students from 3 private high schools in Kuranji District, Padang City. The sampling technique uses total sampling. The data analysis technique used is product moment analysis. The results of this hypothesis test show that the correlation coefficient is r=-0.836 with a significance of p=0.00 (p<0.05). The results of this research show that there is a negative relationship between the quality of school life and truancy behavior among private high school students in Kuranji District, Padang City.